The Effect of Using Think Talk Write (TTW) Strategy toward students’ Speaking Skill for the Tenth Grade Student of Senior High School - Ahmad Zuhri Rosyidi; Fitri Ningsi; Suparlan Suparlan; Darmanto (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research aimed at finding out the effect of Using Think Talk Write (TTW) Strategy toward students’ speaking skill For the Tenth Grade Student of SMA Islam Ulil Albaab NW Lendang Jaran Senior High School. This research was pre experimental research design. The Sample of the study was consisted of 34 students. The Data were gathered by using pre-test and post-test of speaking skill test. In analyzing data, the researcher used SPSS application to count the data. Based on the result of T-Tests, it was founded that the significance result was 0.015 it less than 0, 05. This finding show that Think Talk Write (TTW) effective toward students’ in speaking at the Tenth Grade Student of Senior High School at SMA Islam Ulil Albaab NW Lendang Jaran in the academic year of 2024/2025.